Development of a Lyophilized Off-the-Shelf Mesenchymal Stem Cell-Derived Acellular Therapeutic - Julia Driscoll; Irene K. Yan; Tushar Patel (MDPI AG, 2022)
The therapeutic activities elicited by mesenchymal stem cells (MSC) are in part mediated through paracrine action by the release of extracellular vesicles (EV) and secreted proteins. Collectively, these MSC-derived factors, referred to as the secretome product (SP), are intrinsically therapeutic and represent an attractive alternative to cell-based therapies. Herein, we developed a lyopreservation protocol to extend the shelf-life of the MSC-SP without compromising the structural or functional integrity of the vesicular components. The SP isolated from normoxia- and anoxia-exposed MSC elicited protective effects in an in vitro model of oxidative injury and the bioactivity was retained in the lyophilized samples. Three separate formulations of MSC-SP were isolated by tangential flow filtration using sucrose, trehalose, and mannitol as lyoprotectant agents. The MSC-SPs were lyophilized using a manifold protocol and the structural and functional integrity were assessed. The trehalose formulation of SP exhibited the highest EV and protein recovery after manifold-based lyophilization. To facilitate development as a therapeutic, a shelf lyophilization protocol was developed which markedly enhanced the recovery of EV and proteins. In conclusion, lyophilization represents an efficient method to preserve the structural and functional integrity of the MSC-SP and can be used to develop an off-the-shelf therapeutic.